PELAYANAN KESEHATAN TERHADAP NARAPIDANA DAN TAHANAN SEBAGAI WUJUD PEMENUHAN HAK ASASI MANUSIA (Studi Kasus Rumah Tahanan Negara kelas II B Bangil Pasuruan) - Rizki Syahputra (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This article examines health services for prisoners and detainees as a form of fulfilling Human Rights (case study of Class II B Detention Center Bangil Pasuruan). This research is a juridical-empirical legal research with primary data sources through field studies, observations and interviews, and secondary data through literature review in the form of books, prior research, and review of Law No. 32 of 1999 concerning the Rights of Health services for Prisoners. The results of this study indicate that Class II B Detention Center Bangil Pasuruan has not fully implemented the mandate of Law No. 32 of 1999 concerning routine health checks on prisoners and detainees. However, other efforts have been made by cooperating with the Bangil Community Health Center and Pasuruan District Health Office in handling existing health cases.